Autonomic Remodeling in the Left Atrium and Pulmonary Veins in Heart Failure – Creation of a Dynamic Substrate for Atrial Fibrillation - Ng, Jason (2011)
BACKGROUND: Atrial fibrillation (AF) is commonly associated with congestive heart failure (CHF). The autonomic nervous system is involved in the pathogenesis of both AF and CHF. We examined the role of autonomic remodeling in contributing to AF substrate in CHF. METHODS AND RESULTS: Electrophysiological mapping was performed in the pulmonary veins (PVs) and left atrium (LA) in 38 rapid-ventricular paced dogs (CHF group) and 39 controls under the following conditions: vagal stimulation, isoproterenol infusion, β-adrenergic blockade, acetylcholinesterase (AChE) inhibition (physostigmine), parasympathetic blockade, and double autonomic blockade. Explanted atria were examined for nerve density/distribution, muscarinic receptor (MR) and beta-adrenergic receptor (βAR) densities, and AChE activity. In CHF dogs, there was an increase in nerve bundle size, parasympathetic fibers/bundle, and density of sympathetic fibrils and cardiac ganglia, all preferentially in the posterior LA/PVs. Sympathetic hyperinnervation was accompanied by increases in β(1)AR density and in sympathetic effect on ERPs and activation direction. β-adrenergic blockade slowed AF dominant frequency. Parasympathetic remodeling was more complex, resulting in increased AChE activity, unchanged MR density, unchanged parasympathetic effect on activation direction, and decreased effect of vagal stimulation on ERP (restored by AChE inhibition). Parasympathetic blockade markedly decreased AF duration. CONCLUSIONS: In this heart failure model autonomic and electrophysiologic remodeling occurs involving the posterior left atrium and pulmonary veins. Despite synaptic compensation, parasympathetic hyperinnervation contributes significantly to AF maintenance. Parasympathetic and/or sympathetic signaling may be possible therapeutic targets for AF in CHF.